The Effect of Oil Prices on the Economic Growth of Oil Exporting Countries Bordering the Caspian Sea: Panel Data Analysis - Bolganbayev, Artur; Myrzabekkyzy, Kundyz; Baimaganbetov, Sabit; Kelesbayev, Dinmukhamed (International Journal of Energy Economics and Policy, 2021)
Oil price volatility has increased tremendously in the last decade and has become the most difficult commodity to predict. The price of Brent crude oil was 42 US dollars in 2020, whereas it is 72 dollars today. All countries are adversely affected by this volatility. But the severity of it differs between countries. Especially oil-exporting countries are expected to be affected more negatively. Among the countries bordering the Caspian Sea, the national incomes of Russia, Iran, Kazakhstan, and Azerbaijan are largely based on oil exports; therefore they are heavily affected by the volatility in oil prices. Therefore, energy security, which is one of the most important international security topics, is a political and economic priority for the countries bordering the Caspian Sea. In this study, the effects of the price changes in Brent crude oil on the economic growth and energy security of these countries were examined using Panel data analysis with the quarterly data for the period 2007-2020. The order of integration of the variables discussed in the study is examined using the Pesaran (2007) panel unit root test, which takes the cross-sectional dependence into account. The long-term relationship between Brent oil price and economic growth is examined using the Westerlund (2007) cointegration test. The results show that oil prices affect economic growth. Keywords: Countries Bordering the Caspian Sea, Oil Prices, Economic Growth, Panel Cointegration Test JEL Classications: C33, O47, P42, Q41 DOI: https://doi.org/10.32479/ijeep.11835